Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. The reality of the practice of the principals of public schools in Jeddah Governorate for the interactive theory of leadership and its relationship to the level of administrative creativity they have from their own point of view in light of the Corona pandemic Mrs. Sharefa Ali Alzahrani , Prof. Najat Mohammad Alsaigh 2. King Abdulaziz University students’ compliance with the values of digital citizenship in light of Islamic education directives Prof. Abdullah Attitallah Alahmadi 3. The Effect of Send- A problem Strategy in Acquiring Methods of teaching Concepts and Developing Teamworking Competency of Higher Education Students Dr. Sattar Jabbar Haji 4. The Educational Implications Deduced from the Meccan Forty Hadiths and Their Applications in the Meccan Society – A Field Study on the Workers in the Project of Venerating the Sacred Land – Mr. Faris Abdullah Alhebi 5. The reality of the professional competencies of special education coordinators and teachers working with autism spectrum disorder in the Emirate of Abu Dhabi in the light of quality requirements Dr. Ashraf Mohamed Moustafa , Mrs. Marwa Maher Almelah 6. Mindfulness and its relationship to creative self-efficacy among gifted students in the educational directorates of Hebron Dr. Sawsan Jamal Qabaga 7. The Perception of English Language Teachers of the Importance of e-Learning Platforms in Hebron and Yatta Governorates Mrs. Remah Ali Bhais, Dr. Ibrahim Moh’D Arman, Mr. Awni Moh’D Abu Tair